Extraction optimization, preliminary characterization and immunological activities in vitro of polysaccharides from Elaeagnus angustifolia L. pulp. (20th October 2016) - Du, Hongtao; Chen, Juncheng; Tian, Shan; Gu, Hongling; Li, Na; Sun, Yao; Ru, Jiajia; Wang, Junru
Highlights: The extraction process of EAP was optimized by single factor experiments and RSM. Two homogeneous polysaccharides EAP-1a and EAP-1b were obtained and characterized. EAP could activate macrophages and stimulate macrophage to secrete NO. Effects on macrophages activation were similar between crude EAP and LPS. EAP had the potential to be developed as natural medicines or health foods. Abstract: In this research, extraction optimization, preliminary characterization and immunological activities in vitro of polysaccharides from Elaeagnus angustifolia L. pulp were investigated. A response surface methodology (RSM) with a Box-Behnken design (BBD) was used to optimize the extraction process. The maximum EAP yield was 9.82 ± 0.38%, which is in good agreement with the predicted value (9.93 ± 0.24%). Two homogeneous polysaccharides, EAP-1a and EAP-1b with molecular weights of 8.70 kDa and 4.39 kDa respectively, were prepared by DEAE-52 cellulose and Sephadex G-100 columns and characterized by HPLC, HPGPC, and FT-IR. Three polysaccharides (EAP, EAP-1a and EAP-1b) could stimulate macrophages to release NO and enhance phagocytic activities of RAW 264.7 cells in dose-dependent manner. Moreover, there was no significant difference between crude EAP group (400 μg/mL) and positive control group (LPS) in effects on macrophages. The results implied that EAP had the potential to be developed as natural medicines or health foods.